Impact of fund size on mutual fund performance - Evidence from Finland - Luostarinen, Kaarlo (My University, 2007)
Purpose of the study is to find out the role of economies of scale in the Finnish mu-tual fund market during 2002–2006. Hence, two research questions are explored. The one is the impact of fund size on fund performance. The other is the impact of size change on subsequent performance. To be able to have better understanding of the relationship, different ways to analyze data is used. The study included all the Finnish equity funds investing in Finnish securities dur-ing the sample period. The performance of the funds was examined using three different measures, namely raw return, abnormal return and risk-adjusted return. First, the t-test was used to confirm the possible difference of performance between small (small growth) and large (large growth) funds. Then, those with statistically significant differences were examined further in regression analysis. The results were, to some extend, in line with those of previous studies on the sub-ject. Depending on the measure both positive and negative effect of size was ob-served. However, the evidence of size effect on abnormal return was thoroughly supportive to the hypotheses confirming that fund size erodes abnormal return.
Keywords: mutual fund; fund size; performance; size effect; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|